Half of all out-of-hospital cardiac arrests in public occur in residential areas with lower rates of bystander intervention and survival. (3rd October 2022) - Juul Joergensen, A; Tofte Gregers, M C; Samsoee Kjoelbye, J; Kollander Jakobsen, L; Ettl, F; Krammel, M; Sulzgruber, P; Torp-Pedersen, C; Folke, F; Malta Hansen, C
Abstract: Background: Impressive survival rates have been achieved for public out-of-hospital cardiac arrest (OHCA) in selected areas (airports and similar places), but residential areas as a location for public OHCA remain unexplored. This study aimed to investigate incidence, survival, and bystander intervention when public OHCA occurs in residential areas. Methods: Residential and non-residential areas were defined using Urban Atlas, an open-source database that categorizes urban area surface in the European Union based on land cover use. Residential and non-residential areas were defined based on prespecified Urban Atlas classification. Nature and agricultural areas were excluded. All public OHCAs from 2016–2020 registered with the Danish Cardiac Arrest Registry were included and divided into residential and non-residential areas, excluding OHCAs in nursing homes and medical facilities. The variables have been compared between residential and non-residential areas using the Kruskal Wallis test for non-parametric continuous data and Fischer's exact test for categorical data. A logistic regression model adjusting for age and sex was used to compare bystander cardiopulmonary resuscitation (CPR), bystander defibrillation, and 30-day survival between residential and non-residential areas. A sub-analysis included bystander witnessed OHCAs only. Results: A total of 1, 939 public OHCAs were included, evenly distributed between residential (969 [0.17 OHCA/km 2 /year]) and non-residential areas (970 [0.21 OHCA/km 2 /year]). OHCAs in residential areas differed from those in non-residential areas by having a lower proportion of bystander CPR (84.7% [95% CI: 82.3–86.9%] vs. 88.9% [95% CI: 86.7–90.8%], p-value = 0.007), bystander defibrillation (17.2% [95% CI: 14.9–19.8%] vs. 29.5% [95% CI: 26.6–32.4%], p-value <0.001), and 30-day survival (30.1% [95% CI: 27.2–33.1%] vs. 39.8% [95% CI: 36.7–42.9%], p-value <0.001), respectively. The two groups had similar proportions of shockable rhythm and defibrillation by emergency medical services. Patients with public OHCA in residential areas were older, more likely to be female, have an unwitnessed OHCA, and have a short response time (Table 1). The odds for bystander defibrillation were 50% lower in residential areas than non-residential areas, and the odds for bystander CPR and survival were 30% lower. When only including witnessed public OHCA, the odds remain similar, and the odds of receiving bystander defibrillation and surviving were still significantly lower than non-residential areas (Figure 1). Conclusion: Half of all OHCAs in public occur in residential areas. They are less likely to receive bystander interventions and have a lower likelihood of 30-day survival compared to public OHCAs in non-residential areas. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Tryg Foundation